The Janus-faced nature of time spent on homework: Using latent profile analyses to predict academic achievement over a school year. (October 2015) - Flunger, Barbara; Trautwein, Ulrich; Nagengast, Benjamin; Lüdtke, Oliver; Niggli, Alois; Schnyder, Inge
Abstract: Homework time and achievement are only modestly associated, whereas homework effort has consistently been shown to positively predict later achievement. We argue that time spent on homework can be an important predictor of achievement when combined with measures of homework effort. Latent profile analyses were applied to a longitudinal data set with 1915 eighth-grade students who had been surveyed on their homework behavior in French as a second language. There were three main findings. First, based on their values for homework time and homework effort, five distinct learning types were identified: fast learner, high-effort learner, average student, struggling learner, and minimalist . Second, latent transition analyses confirmed that these learning types were stably identified over time. Third, longitudinal analyses predicting Time 2 academic achievement indicated that time spent on homework can be associated with positive (as in the high-effort learner ) and negative (as in the struggling learner ) outcomes. Highlights: Five groups of students with different homework behavior profiles identified. Homework learning types were relatively stably identified over time. Differential associations of students' homework learning type to their achievement. A better understanding of homework time was yielded via a person-centered approach.